2017
DOI: 10.1002/ange.201702901
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Copper–Oxygen Mediated C−H Bond Activation by the Formylglycine‐Generating Enzyme

Abstract: The formylglycine-generating enzyme (FGE) is aunique copper protein that catalyzes oxygen-dependent C À H activation. We describe 1.66 -a nd 1.28 -resolution crystal structures of FGE from Thermomonospora curvata in complex with either Ag I or Cd II providing definitive evidence for ahigh-affinity metal-binding site in this enzyme.The structures reveal ab is-cysteine linear coordination of the monovalent metal, and tetrahedral coordination of the bivalent metal. Similar coordination changes may occur in the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Specifically, FGE converts sulfatase cysteines or serines within a conserved [C/S]-X-P-X-R motif to formylglycine (48)(49)(50). This oxygen-dependent reaction relies on two active site cysteines to coordinate a copper ion, which in turn binds the FGE substrate and primes it for reaction with oxygen (51)(52)(53). Notably, we found that Tsi3 homologs lack the catalytic cysteines essential to FGE function (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Specifically, FGE converts sulfatase cysteines or serines within a conserved [C/S]-X-P-X-R motif to formylglycine (48)(49)(50). This oxygen-dependent reaction relies on two active site cysteines to coordinate a copper ion, which in turn binds the FGE substrate and primes it for reaction with oxygen (51)(52)(53). Notably, we found that Tsi3 homologs lack the catalytic cysteines essential to FGE function (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…The striking relatedness of Tsi3 homologs to FGE domain-containing proteins suggests that these proteins likely share a common ancestor. Crystal structures from several FGE homologs indicate that the FGE domain adopts a unique “FGE fold” with low secondary structure (<20% of each β-sheets and α-helices) (49, 50, 52, 53, 63, 64). The FGE fold is also found in the X-ray crystal structures of non-FGE enzymes, including the putative oxidoreductase PvdO and the sulfoxide synthase EgtB.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption band at 600 nm from the coordination of cysteine to T1 Cu disappeared at high Ag + concentrations. Additionally, the inhibition of copper enzymes often involves the substitution of Cu + in the catalytic site by Ag + because of the analogous behavior of these two ions [24][25][26]. Table 2 lists the BOD activity with the addition of various Ag + solutions, demonstrating that the inhibition of T1 Cu decreased the enzymatic activity.…”
Section: Binding Of Ag + To Bodmentioning
confidence: 99%
“…A Dali search revealed that the N -terminal domain most closely resembles the damage-inducible protein Din-B (PDB ID: 5WK0 ) and the C -terminal domain is structurally similar to the formylglycine generating enzyme (PDB ID: 5NXL). The C -terminal domain shares a high structural similarity with the catalytic domain of EgtB Mth …”
mentioning
confidence: 99%